THE INFLUENCE OF SOWING DATES, SEEDING RATES AND PLANTING METHODS ON THE ACCUMULATION OF DRY MASS IN BUCKWHEAT CULTIVATED AS A SECOND CROP - Isroilov Bakhtiyor Abdullayevich (Modern American Journals, 2025)
This article presents data on the effect of sowing dates, seeding rates, and planting methods on the accumulation of dry mass in buckwheat cultivated as a second crop. It was observed that the dry mass per plant was higher in variants with single-row sowing across different sowing dates, ranging from 25.0 to 30.2 g/plant. Conversely, the dry mass yield per hectare was determined in variants with three-row sowing across all sowing dates, ranging from 42.6 to 50.8 q/ha. The highest accumulation of dry mass was observed in the variant sown on June 20 with a single-row method at a rate of 1 million seeds/ha. The accumulation of dry mass across development phases was as follows: 3.6 g/plant in the tillering phase, 8.9 g/plant in the panicle emergence phase, 13.2 g/plant in the flowering phase, and 30.2 g/plant in the fruit formation phase.
Keywords: Buckwheat, as a second crop, sowing date, seeding rate, planting method, dry mass, developmental phase.